ANALISIS STRUKTURALISME LEVI-STRAUSS TERHADAP KISAH PEDAGANG DAN JIN DALAM DONGENG SERIBU SATU MALAM - Neneng Yanti Kh. (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
Seribu Satu Malam (One thousand and One Nights or The Arabian Nights) is a renowned tale through out the world, which has been translated into languages. As a literarywork, it certainly has a unique structural characteristic. The aim of this paper is to analyze the unique structure of Seribu Satu Malam based on Levi-Strauss’ Structuralism. It analyses one of the Seribu Satu Malam stories as a sample; that is Kisah Pedagang dan Jin (the story of the trader and the genie). In the stories of Kisah Pedagang dan Jin, its structure can be found in the all of Seribu Satu Malam stories. This study reveals the threads of ceritheme, which connects one story to the others until those stories appeared as a unity. The stories are seen as variations of a single theme, which is how the characters saw their own life and solved their problems. This becomes the stories’ hidden structures.